Nanostructured Lipid Carrier for Topical Application of N-Acetyl Glucosamine - Lavin Aliasgharlou; Saeed Ghanbarzadeh; Hamideh Azimi; Mohammad Hossein Zarrintan; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2016)
Purpose: Hyperpigmentation occurs when melanin is overproduced in certain spots on the skin and is one of the most challenging skin conditions to treat. Although it is usually harmless, for cosmetic reasons, it is dreadfully bothersome to those who undergo it. It was reported that N-acetyl-glucosamine (NAGA) prevents melanin synthesis and alters the expression of numerous genes related to pigmentation. In spite of these advantages, NAGA cannot be employed in topical formulations due to its extremely polar characteristics. Nanoparticles, especially lipid-based ones, have been introduced as an efficient carrier for dermal drug delivery. Methods: The aim of the present study was to load adequate hydrophilic NAGA to the lipophilic nanostructured lipid carriers (NLCs) for potential dermal application. Methods: NAGA-loaded NLCs were formulated, using hot homogenization technique, and the characteristics of the optimized formulation were analyzed by laser light scattering, X-ray diffraction, and scanning electron microscopy methods. Loading capacity percentage and in vitro release study were carried out by applying a validated HPLC method. The optimum formulation was utilized for the in vivo skin lightening evaluations in healthy volunteers. Results: NAGA-loaded NLCs demonstrated promising results (the size of 190 nm, narrow size distribution, loading capacity of 9%, and appropriate NAGA release profile) suitable for dermal delivery. XRD results exhibited a dramatic reduction in the crystalline structure of encapsulated NAGA. Dermoscopy images indicated a considerable decline in melanin distribution pattern in the majority of the cases treated with NAGA-loaded NLCs. Conclusion: Thus, this study has opened new horizons for the potential use of lipid based nanoparticles in the managing of hyperpigmentation.